Challenges and Strategies to Advance High‐Energy Nickel‐Rich Layered Lithium Transition Metal Oxide Cathodes for Harsh Operation. (9th September 2020) - Xu, Gui‐Liang; Liu, Xiang; Daali, Amine; Amine, Rachid; Chen, Zonghai; Amine, Khalil
Abstract: Nickel‐rich layered lithium transition metal oxides (LiNi1− x − y Co x Mn y O2 and LiNi1− x − y Co x Al y O2, x  + y  ≤ 0.2) are the most attractive cathode materials for the next generation lithium‐ion batteries for automotive application. However, they suffer from structural/interfacial instability during repeated charge/discharge, resulting in severe performance degradation and serious safety concerns. This work provides a comprehensive review about challenges and strategies to advance nickel‐rich layered cathodes specifically for harsh (high‐voltage, high‐temperature, and fast charging) operations. Firstly, the degradation pathways of nickel‐rich cathodes including surface/interface degradation, undesired cathode–electrolytes parasitic reactions, gas evolution, inter/intragranular cracking, and electrical/ionic isolation are discussed. Then, recent achievements in stabilizing the structure/interface of nickel‐rich cathodes via surface coating, cation/anion doping, composition tailoring, morphology engineering, and electrolytes optimization are summarized. Moreover, challenges and strategies to improve the performance of Ni‐rich cathodes at the electrode level are discussed. Outlook and perspectives to promote the practical application of nickel‐rich layered cathodes toward automotive application are provided as well. Abstract : This review is aimed at a comprehensive discussion on the challenges and strategies (material/electrode structures and interphase) to advance the application of Ni‐rich cathodes for harsh operation (high Ni content, high voltage, high temperature, and high rate).